Is There a Need for a 6-Month Postradiosurgery Magnetic Resonance Imaging in the Treatment of Vestibular Schwannoma?. Issue 2 (12th April 2019) - Perry, Avital; Graffeo, Christopher S; Carlstrom, Lucas P; Hughes, Joshua D; Peris-Celda, Maria; Cray, Nealey M; Pollock, Bruce E; Link, Michael J
Abstract: BACKGROUND: Stereotactic radiosurgery (SRS) is a common treatment modality for vestibular schwannoma (VS), with a role in primary and recurrent/progressive algorithms. At our institution, routine magnetic resonance imaging (MRI) is obtained at 6 and 12 mo following SRS for VS. OBJECTIVE: To analyze the safety and financial impact of eliminating the 6-mo post-SRS MRI in asymptomatic VS patients. METHODS: A prospectively maintained SRS database was retrospectively reviewed for VS patients with 1 yr of post-treatment follow-up, 2005 to 2015. Decisions at 6-mo MRI were binarily categorized as routine follow-up vs clinical action —defined as a clinical visit, additional imaging, or an operation as a direct result of the 6-mo study. RESULTS: A total of 296 patients met screening criteria, of whom 53 were excluded for incomplete follow-up and 8 for NF-2. Nine were reimaged prior to 6 mo due to clinical symptoms. Routine 6-mo post-SRS MRI was completed by 226 patients (76% of screened cohort), following from which zero instances of clinical action occurred. When scaled using national insurance database-derived financials—which estimated the mean per-study charge for MRI of the brain with and without contrast at 1767—the potential annualized national charge reduction was approximated as 1 611 504. CONCLUSION: For clinically stable VS, 6-mo post-SRS MRI does not contribute significantly to management. We recommend omitting routine MRI before 12 mo, in patients without new or progressive neurological symptoms. If extrapolated nationally to the more than 100 active SRS centers, thousands of patients would be spared an inconvenient, nonindicated study, and national savings in health care dollars would be on the order of millions annually.